Looking in the Right Places: Minority-Serving Institutions as Sources of Diverse Earth Science Learners. Issue 4 (1st November 2017) - McDaris, John R.; Manduca, Cathryn A.; Iverson, Ellen R.; Orr, Cailin Huyck
ABSTRACT: Despite gains over the last decade, the geoscience student population in the United States today continues to lag other science, technology, engineering, and mathematics disciplines in terms of diversity. Minority-serving institutions (MSIs) can play an important role in efforts to broaden underrepresented student engagement with Earth Science content, especially in collaborations with other institutions and organizations that allow MSIs to share their expertise. Knowing which MSIs have Earth-related degree programs can help facilitate such collaboration. This commentary describes an effort to find and raise the visibility of these programs. In 2013, the abundance of geoscience departments at MSIs was roughly half that seen in U.S. higher-education institutions. Yet we found that nearly a third of MSIs offered one or more Earth-related degree programs. In addition, more than half of the academic units offering Earth-related degrees were interdisciplinary rather than traditional geoscience departments. It is clear that students are learning about the Earth in a wider variety of places than geology programs. These programs could provide models for supporting diverse students in the geosciences, as well as sites for potential collaborations aimed at further increasing the diversity of the geoscience workforce.